As crianças e o seu recreio escolar : um estudo etnográfico sobre a ludicidade na terceira infância - Juliani, Moacir (2019)
This research aims to understand the school playground as a space-time of manifestation of playing culture, as well as the relationships maintained beyond the classroom, in terms of formative conserning. Another important objective is to recognize the playing cultures that appear during recess, from their ethological nature, their rites and negotiations. Analyzing the relationships that are linked to creative leisure, developed in the same spacetime. What do these children play? What's fertile in these activities? What creativity emerges from this autotelism? What specificities of playful culture are manifested today? These were some questions the research faced, electing a theoretical framework which would help us in the organization of the subject. Reading Brougère, Château, Manson, Smith, Gomes, and others, we can have been able to identify the common jokes between boys and girls, their relationships, and their rhetoric. An ethnographic research was carried out, using as loci a public school, one school of the private network and another confessional school, in the city of Cuiabá, in Mato Grosso State. The subjects of choice are the students of the early childhood. With the work, it was possible to see how the school extrapolation goes beyond the idea that playfulness is expressed only in children's games, manifesting itself especially through the scenic game, the simulacrum, within the game of relations. It was possible to see the game of life, represented by these games, by this “playful impulse”, as Marcuse (1975) would say, is also enhanced by a “playful complicity” present in today's school playground; in the students' opposition to the constituted authorities; in gender disputes; in the hierarchization of groups and singularization of subjects and their identities, to remember Mcluran (1991); in re-producing games similar to those in the neighborhood. All this manifestation has equipped us to think that the playground and the real world, which materializes within the school, underlies a discourse that is situated in progress while students show the rhetoric of the self and the school – an institution responsible for the construction of formal learning – needs to look at the playground as a window from which they can see ways playful culture can contribute to its proposal for human formation.